Perdarahan Saluran Cerna Atas Pascaoperasi Whipple Dengan Komplikasi Fistula Pankretokutan: Komplikasi Langka Dan Peran Oktreotid Sebagai Terapi Efektif - Indrayani, Made; Andari Kluniari , Ni Made Nova (Green Publisher Indonesia, 2025)
Whipple's postoperative gastrointestinal bleeding is a rare but fatal complication. Diagnosis and management of Whipple's postoperative slow-type bleeding with complications of pancretocutaneous fistula is often challenging due to atypical clinical manifestations and complex postoperative anatomy. Case Report: A 28-year-old male patient came in with black chapters, abdominal pain, nausea and vomiting since 2 weeks earlier. The patient underwent Whipple surgery 6 years ago with complications of pancreatocutaneous fistula. Despite having undergone fistula closure surgery 3 years ago, the fistula reopened and produced a clear, yellowish fluid. Patients exhibit conditions of hemodynamic instability, clinical dehydration and anemia. Computed tomography (CT)-scan showed the presence of necrotic pancreatitis. Despite receiving blood transfusions and supportive therapy, the patient still experiences black chapters and hemoglobin levels continue to decline. The patient then received additional therapy with intravenous octreotides where the patient showed clinically significant improvement characterized by cessation of black chapters and decreased fistula production. Conclusion: Gastrointestinal bleeding is one of the complications that can occur years after Whipple's surgery. These complications are often associated with the formation of pancreatic fistulas that cause vascular erosion, pseudoaneurysm formation, and prolonged inflammation. Therefore, in these cases, octreotides can be considered as an adjuvant therapy that not only helps to stop bleeding, but can also help decrease the secretion of pancreatic fluid and the closure of the fistula.